Developing A Medical Record Information System To Improve The Quality Of Health Services For Primary School Students - Asharul Fahyudi, Joko Sutarto, Joko Widodo, Edy Purwanto (South Eastern European Journal of Public Health, 2025)
Introduction: School health services are essential to improving student health. Based on previous studies, no school health service has developed a student personal medical record information system to support effective health monitoring and intervention, especially for primary school (PS) students. Objevtives: The objectives this study is to develop a medical record information system that improves primary school students' health services and enhances health data management's efficiency and effectiveness through a user-friendly and systematic approach. Methods: This type of research is research and development (R&D) using the ADDIE model, with five phases: analysis, design, development, implementation, and evaluation. Results: These findings underscore the importance of integrating technology into school health services and highlight the SIREKA model's potential benefits in improving elementary school students' health management. This is the first study to develop Developing a Medical Record Information System to Improve the Quality of Health Services for Primary School Students. Conclusions: Conclusion underscore the importance of the SIREKA model in improving health services for PS students and highlight the need for continuous evaluation and improvement of the system. The SIREKA model was positioned to significantly enhance the quality of health services provided to PS students, demonstrating its potential for widespread adoption in educational settings. The SIREKA model contributes significantly to the quality of health services for PS students by providing a structured framework for health data management, integrating health services, and ensuring that the model is tailored to meet user needs effectively.